Protection of the right of real servitude according to local and international legislation and practice (Revista de Investigaciones Universidad del Quindío, 2022)
The right of servitude as a real right enjoys the same rights as other real rights. Among these rights is the protection of the right of servitude in case it is violated by persons who are not holders of this right. Based on the local legislation as well as that of other countries, the holder of the right of easement has the right to protect the right of easement in case that right is violated by someone else, and not only the holder of the right but also the owner of the servient property in case it finds that the holder of the right of servitude does not use the right that he has, or in the case that he finds that the holder of the right of servitude uses that right causing damage to the owner of the servient property! All this based on the judicial practice that the parties seek the protection of the right of real servitude, as well as the right holder and the owner of the servient property, we have tried to show through this paper in short points how a right can be protected of real servitude based on local law and that of international countries!
Keywords: easement right; real easement; protection of real easement; self-defense; court decision